Astrocyte scar formation aids CNS axon regeneration - Anderson, Mark A. (Nature, 2016)
Transected axons fail to regrow in the mature central nervous system (CNS). Astrocyte scars are widely regarded as causal in this failure. Here, using three genetically targeted loss-of-function manipulations in adult mice, we show that preventing astrocyte scar formation, attenuating scar-forming astrocytes, or deleting chronic astrocyte scars all failed to result in spontaneous regrowth of transected corticospinal, sensory or serotonergic axons through severe spinal cord injury (SCI) lesions. In striking contrast, sustained local delivery via hydrogel depots of required axon-specific growth factors not present in SCI lesions, plus growth-activating priming injuries, stimulated robust, laminin-dependent sensory axon regrowth past scar-forming astrocytes and inhibitory molecules in SCI lesions. Preventing astrocyte scar formation significantly reduced this stimulated axon regrowth. RNA sequencing revealed that astrocytes and non-astrocyte cells in SCI lesions express multiple axon-growth supporting molecules. Our findings show that contrary to prevailing dogma, astrocyte scar formation aids rather than prevents CNS axon regeneration.